Particularities of the Implement of Quality Management System Based on the Requirements of the ISO 9001 in the Telecommunications Companies; International Review of Management and Marketing; Vol. 6, iss. 3 - Verkhovskaya M. V. Marina Vitalievna (2016, 2016)
Title screen